Now or never: will COVID-19 bring about water and sanitation reform in Dharavi, Mumbai?. Issue 8 (3rd August 2021) - Saha, Ria; Kajal, Fnu; Jahan, Nuzrath; Mushi, Vivian
ABSTRACT: Even with the established clinical effectiveness of the vaccines worldwide, published reports show the evidence of recurrent Corona Virus Disease-2019 (COVID-19) infections among those who are already vaccinated. Hence, safe hand wash practice for 20 s and recommended physical distancing are the two essential swords to defeat the deadly contagion. But in the communities of Dharavi, an urban slum in Mumbai, India, the accessibility to and attainment of safe handwashing and physical distancing are hugely impaired by poorly maintained and deteriorating Water, Sanitation and Hygiene (WaSH) infrastructure. This grave condition along with the disastrous second wave amplifies the already existing susceptibility and vulnerabilities of the communities to the fear of infection and its consequent acquisition. Women are disproportionately affected by this pressing condition. Accessibility to and affordability of safe WaSH services are the two fundamental challenges faced by the communities. Dharavi is currently witnessing a horrendous second wave and thus needs immediate attention by both national and state level policy makers. Since these two challenges render the community more vulnerable to the infection, here in this commentary, we delineate a sustainable roadmap to overcome these two pivotal challenges. The state government should immediately prioritise this issue in the local level policy making to prevent any additional unwanted (avoidable) poor WaSH (hygiene) related COVID-19 deaths and mitigate any associated health risks.